Study of mirror effect on scrape‐off layer‐divertor plasma based on a generalized fluid model incorporating ion temperature anisotropy. Issue 6 (18th May 2018) - Togo, S.; Takizuka, T.; Reiser, D.; Hoshino, K.; Ibano, K.; Li, Y.; Ogawa, Y.; Sakamoto, M.; Ezumi, N.; Nakashima, Y.
Abstract : The mirror effect on scrape‐off layer (SOL)‐divertor plasma profiles was studied by relaxing the assumption of homogeneous magnetic fields used in a one‐dimensional (1D) plasma fluid model, which incorporates the anisotropic ion temperature. For collisionless plasmas, the perpendicular ion temperature proportional to the magnetic field strength is observed, which reflects the conservation of the magnetic moment. In diverging field cases, the plasma flow becomes supersonic, while it is kept subsonic in contracting field cases. Parallel momentum gains/losses and energy transfers between parallel and perpendicular components caused by the mirror effect are also observed. In addition, it is indicated that the viscous flux approximation is invalid in inhomogeneous magnetic fields regardless of the plasma collisionality.